2011
DOI: 10.1007/s00464-011-1735-9
|View full text |Cite
|
Sign up to set email alerts
|

The impact of preventable disruption on the operative time for minimally invasive surgery

Abstract: This report demonstrates that preventable disruption caused an increase in operative time and forced surgeons and patients to endure unnecessary delay of more than 32%. Such additional time could be used to deal with the pressure of emergency cases and to reduce waiting lists for elective surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 19 publications
(33 reference statements)
0
31
0
Order By: Relevance
“…We relied on literature on human factors, patient safety, and operating theatre techniques (Barnes, 1980;Dankanich;Karwowski and Salvendy, 2010;Meyers and Stewart, 2002;Philips, 2004;Wachter, 2012) as well as on our team's ergonomics and clinical experience to select and adapt the traditional principles. In addition, we consulted related research studies on surgery (Al-Hakim, 2011;Al-Hakim and Gong, 2012;Berguer, 1999;Etchells et al, 2003;He et al, 2013;Jaschinski et al, 1998;Manasnayakorn et al, 2009;Moorthy et al, 2005;Sevdalis et al, 2007;Stifelman et al, 2001;van Det et al, 2009;van Veelen et al, 2002;Vereczkei et al, 2004;Wiegmann et al, 2007;Wong et al, 2011;Zheng et al, 2007) to develop new areas and principles for motion economy.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We relied on literature on human factors, patient safety, and operating theatre techniques (Barnes, 1980;Dankanich;Karwowski and Salvendy, 2010;Meyers and Stewart, 2002;Philips, 2004;Wachter, 2012) as well as on our team's ergonomics and clinical experience to select and adapt the traditional principles. In addition, we consulted related research studies on surgery (Al-Hakim, 2011;Al-Hakim and Gong, 2012;Berguer, 1999;Etchells et al, 2003;He et al, 2013;Jaschinski et al, 1998;Manasnayakorn et al, 2009;Moorthy et al, 2005;Sevdalis et al, 2007;Stifelman et al, 2001;van Det et al, 2009;van Veelen et al, 2002;Vereczkei et al, 2004;Wiegmann et al, 2007;Wong et al, 2011;Zheng et al, 2007) to develop new areas and principles for motion economy.…”
Section: Methodsmentioning
confidence: 99%
“…However, the literature reveals that errors also commonly occur in surgical procedures performed by experienced surgeons and operative teams (Al-Hakim, 2011;Joice et al, 1998;Sevdalis et al, 2008;Wiegmann et al, 2007). EEM identifies and describes errors (e.g., using wrong instrument) but does not provide the root cause or actual circumstance that drives or forces a surgeon to act erroneously.…”
Section: Hierarchical Task Analysis and Human Error Identification Tementioning
confidence: 97%
See 2 more Smart Citations
“…We feel that what is required in studies such as the one reported by Gillespie et al 1 is a prospective assessment of the actual wasted time during an operation, and ideally also the effect of a disruptive event on operative time 2. We agree that higher incidence of specific disruptions will likely have a bigger impact on operative time, but the magnitude of the impact is likely to depend upon the type of disruption 3 4.…”
mentioning
confidence: 88%